PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM UNTUK MENINGKATKAN HASIL BELAJAR TENTANG JENIS-JENIS USAHA EKONOMI SISWA - Afif Alwan (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2026)
The problem in this study is student achievments of under  standard of minimum completeness achievements of fifth grade students. This study object process and result learning achievements using the flipped classroom model. The approach used is a qualitative approach and this type of research is Classroom Action Research (CAR). The implementation of this research action was carried out in 2 cycles starting with pre-action activities then in each cycle consisting of 4 stages which included planning, implementation, observation, and reflection. Meanwhile, to determine the percentage level of student achievments , researchers used observation sheets and final evaluation tests in each cycle. The subjects in this study were teachers and students of class V UPTD SD Negeri 48 Barru in the academic year 2022/2023 totaling 24 students consisting of 12 male and 12 female. Data analysis was carried out during and after data collection. In the first cycle the research results on the learning process were in good qualification (C) and the student achievments  in sufficient  qualification (C) while in the second cycle the research results on the learning process were in good qualification (B).  and the student achievments in sufficient  qualification (B). The conclusion of  this study is that the application of the flipped classroom learning model can improve the process and student learning outcomes about types of economic business in class V UPTD SD Negeri 48 Barru.